1997
DOI: 10.1097/00001888-199708000-00015
|View full text |Cite
|
Sign up to set email alerts
|

A pilot course as a model for implementing a PBL curriculum

Abstract: Many medical schools are shifting to a problem-based learning (PBL) curriculum, some without any transition period, others using periods of parallel-track curricula. The authors report on and discuss a third strategy for implementing PBL: using a pilot course as a model to facilitate the transition. After the Université de Montréal Faculty of Medicine chose to switch PBL, one course in the third year of the traditional curriculum was changed to PBL format 11 months before the new curriculum was to start in Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There are only 15 publications that analyze the satisfaction of tutors, most of them surveys or questionnaires [ 85 , 88 , 92 , 98 , 108 , 110 , 119 ]. In comparison with the satisfaction of the students, here the results are more neutral [ 112 , 113 , 115 , 120 , 121 ] and even unfavorable to the PBL methodology in two publications [ 117 , 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are only 15 publications that analyze the satisfaction of tutors, most of them surveys or questionnaires [ 85 , 88 , 92 , 98 , 108 , 110 , 119 ]. In comparison with the satisfaction of the students, here the results are more neutral [ 112 , 113 , 115 , 120 , 121 ] and even unfavorable to the PBL methodology in two publications [ 117 , 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…31 Experiences at Harvard and at the University of Hawaii have been recorded by Moore 22 and Anderson. 32 One approach to the introduction of a PBL curriculum is the initial introduction of a "pilot" program, 33 or "parallel track" program, as was initiated at University of Southern California 1-2 in 1995. The introduction of a PBL pedagogy requires the completion of several essential events to prepare both the dental faculty and the school facility for the optimal environment for the pedagogy.…”
Section: Clinical Skill Progression In a Pbl Curriculummentioning
confidence: 99%
“…The most frequent methodology were surveys or questionnaires (29 studies) followed by comparative studies with traditional or lecture-based methodology (19 studies, 7 of them were randomized). Almost all the studies (47) have shown that PBL is generally well-received (Sokas et al 1990;Blosser & Jones 1991;Usherwood 1991;Bernstein et al 1995;Kaufman & Mann 1996;Kalaian & Mullan 1996;Gresham & Philp 1996;Vincelette 1997;Kaufman & Mann 1999;Antepohl & Herzig 1999;Casassus et al 1999;Purdy et al 1999;Farrell et al 1999;Ghosh & Dawka 2000;Dyke et al 2001;Walters 2001;Leung et al 2001;Khoo et al 2001;Villamor 2001;Curtis et al 2001;Trevena & Clarke 2002;Chang et al 2004;McLean 2004;Casey et al 2005;Abu-Hijleh et al 2005;Lucas et al 2006;Burgun et al 2006;Gurpinar et al 2009;Suleman et al 2010;Wang et al 2010;Tian et al 2012;Elzubeir 2012;Sulaiman & Hamdy 2013;Albarrak et al 2013;Li et al 2013;Meo 2014;Khoshnevisasl et al 2014;Nosair et al 2015;González et al 2015;Tshitenge et al 2017;…”
Section: Student Satisfactionmentioning
confidence: 99%
“…These include unclear communication of the learning methodology, objectives and assessment method; bad management and organisation of the sessions; tutors having little experience of the method; and a lack of standardisation in the implementation of the method by the tutors. Tutor satisfaction There are only 12 publications that analyze the satisfaction of tutors, most of them surveys or questionnaires (Bernstein et al 1995;Vincelette et al 1997;Khoo et al 2001;Gurpinar et al 2009). In comparison with the satisfaction of the students, here the results are more neutral (Macallan et al 2009;Subramaniam et al 2014;Khan & Al-Swailmi 2015;Chang 2016;Yoo et al 2019) and even unfavorable to the PBL methodology in two publications (Gri th et al 1996;De Lowerntal 1996).…”
Section: Student Satisfactionmentioning
confidence: 99%